Komunikasi Politik Partai Keadilan Sejahtera Pada Masyarakat Non Muslim Di Kabupaten Karawang - Agus Muhidin; Wahyu Utami Dewi; Nurkinan Nurkinan (Peneliti.net, 2022)
This study aims to study and find out about the Political Communication of the Prosperous Justice Party in non-Muslim communities in Karawang Regency. The theory used is Political Communication and Nimmo with five main elements which include, communicator, message, media, audience and effect. This research is a qualitative type with the technique of determining the informants carried out by snowball sampling. Data collection techniques in this study were carried out through triangulation which included interviews, observations and documentation studies. The result of this study is that communicators in PKS communication in gaining votes among non-Muslims are carried out by three figures, namely PKS cadres as politicians, scholars as professionalism and the success team as activists. The political message that is built is a promise, the media used are digital media and direct field media. The mass audience is disorganized and the effect obtained is not optimal, because there is still a lack of voice and enthusiasm from non-Muslim groups towards political communication used by PKS.